When the water tap runs dry - Meyer, Ron.; Centre Communications (New York : Ambrose Video Publishing, 2009)
The greatest impacts from climate change will not be warmer temperatures but water shortages. Learn how America's water infrastructure is incapable of handling these changes. There exist solutions that will make us rethink everything from how we use water, to where we live, to who owns water. Every drop of water that flows through America's rivers or is stored in our lakes and reservoirs is spoken for. Now, America is over-drafting its water supply. How did it come to this? The answers lie in America's outdated water infrastructure, an inflexible water storage system, greater demand from an increasing population and the impacts of global warming. In When the Water Tap Runs Dry, we will look at these issues and provide essential solutions based on a new vision of America's water infrastructure, and customized water rights agreements. If the water crisis is not addressed, the water tap will run dry for many Americans.
Videographers, Ron Meyer, Kenny James, Michael Ramsey, Diane Evans ; editor, Kenny James ; original music, David Arkenstone.
Narrator: Alphonse Keasley.
DVD format.
Keywords: Water resources development -- Environmental aspects -- United States; Water-supply -- United States; Water consumption -- United States; Water conservation